Megatron is put to the test - Cruz, Gloria (Ready-to-read. Superstar reader!, 2024)
When Dr. Meridian captures Megatron and Dot Malto, Megatron is put to the test. Will he keep his oath and stay loyal to Optimus Prime and help save Robby and Mo's mom, or will he go back to his old ways and side with Meridian?